PENETAPAN HARGA HASIL PERIKANAN DALAM PERSPEKTIF EKONOMI ISLAM (STUDI KASUS PASAR PELELANGAN IKAN KOTA KENDARI) - Aswawi, Nurafiah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The purpose of this study is to determine and analyze the pricing of fishery products from an Islamic economic perspective (Case study in the Kendari City fish auction market which: 1. Explains the price fixing mechanism for the sale of fishermen's catch that occurs in the Kendari City Fish Auction Market. Explain the Islamic economic perspective on the fish price fixing mechanism for fishermen at the Kendari City Fish Auction Market. This research method is qualitative with a sosoilogical economic approach. The data sources in this study were fishermen, skippers, and fish collectors. Data collection methods used were interviews, documentation and reference tracing. The technique of collecting data management and analysis was carried out by conducting in-depth interviews with informants. The results of this study indicate that the price fixing that occurs at the Kendari City fish auction cannot be said to be in accordance with Islamic law because although initially there was cooperation between two parties, namely the skipper as the provider of capital and the fisherman as the manager, but in terms of pricing, only one party was involved. can determine that is the skipper.